Direct Identification of Staphylococcus aureus and Determination of Methicillin Susceptibility From Positive Blood-Culture Bottles in a Bact/ALERT System Using Binax Now S. aureus and PBP2a Tests - Heraud, Sandrine (Ann Lab Med, 2015)
Staphylococcus aureus bacteremia is associated with high mortality and morbidity, requiring prompt and appropriate antimicrobial treatment. Therefore, it is important to detect methicillin-resistant S. aureus (MRSA) rapidly from blood cultures. Two immunochromatographic tests, BinaxNow S. aureus and BinaxNow PBP2a, were directly applied to 79 Bact/Alert bottles that were positive for Gram positive cocci in cluster aggregations. Sensitivity and specificity for the identification of S. aureus and determination of methicillin resistance were 94% and 87%, and 100% and 100%, respectively, with less than 30 min of performance time. These tests are efficient and rapid; these tests are valuable alternatives to more sophisticated and expensive methods used in the diagnosis of MRSA bacteremia.